Z-DNA as a Touchstone for Additive Empirical Force Fields and a Refinement of the Alpha/Gamma DNA Torsions for AMBER - Zgarbová, Marie; Šponer, Jiří; Jurečka, Petr (Journal of chemical theory and computation, 2021)
Although current AMBER force fields are relatively accurate for canonical B-DNA, many noncanonical structures are still described incorrectly. As noncanonical motifs are attracting increasing attention due to the role they play in living organisms, further improvement is desirable. Here, we have chosen the Z-DNA molecule, which can be considered a touchstone of the universality of empirical force fields, since the noncanonical α and γ backbone conformations native to Z-DNA are also found in protein-DNA complexes, i-motif DNA, and other noncanonical DNAs. We show that spurious α/γ conformations occurring in simulations with current AMBER force fields, OL15 and bsc1, are largely due to inaccurate α/γ parametrization. Moreover, stabilization of native Z-DNA substates involving γ = trans conformations appears to be in conflict with the correct description of the canonical B-DNA structure. Because the balance of the native and spurious conformations is influenced by nonadditive effects, this is a difficult case for an additive dihedral energy scheme such as AMBER. We propose new α/γ parameters, denoted OL21, and show that they improve the stability of native α/γ Z-DNA substates while keeping the canonical DNA description virtually unchanged, thus representing a reasonable compromise within the additive force field framework. Although further extensive testing is needed, the new modification appears to be a promising step toward a more reliable description of noncanonical DNA motifs and provides the best performance for Z-DNA molecules among current AMBER force fields.
Keywords: DNA, B-Form; Molecular Dynamics Simulation; konformace nukleové kyseliny; Nucleic Acid Conformation; simulace molekulární dynamiky; B-DNA; DNA, Z-Form; Z-DNA